2D Perovskite Heterojunction‐Based Self‐Powered Polarized Photodetectors with Controllable Polarization Ratio Enabled by Ferro‐Pyro‐Phototronic Effect - Xiaoran Yang; Binyi Zhou; Meitong Guo; Yao Liu; Ridong Cong; Leipeng Li; Wenqiang Wu; Shufang Wang; Linjuan Guo; Caofeng Pan; Zheng Yang (Advanced Science)
Abstract Metal halide perovskites (MHPs) are commonly used in polarization‐sensitive photodetectors (PDs) for applications such as polarization imaging, remote sensing, and optical communication. Although various methods exist to adjust the polarization‐sensitive photocurrent, a universal and effective approach for continuous control of MHPs’ optoelectronic and polarized properties is lacking. A universal strategy to electrically modulate the polarization ratio (PR) of self‐powered polarized PDs using the ferro‐pyro‐phototronic effect (FPPE) in 2D perovskites is presented. By varying the amplitude and direction of ferroelectric polarization voltage, the built‐in electric field in the heterojunction can be modulated, allowing for controllable PR regulation and adjustable polarization characteristics. Moreover, the polarized pyroelectric photoresponses are realized, significantly enhancing the responsivity, response speed of the polarized PDs. Both the pyroelectric currents and photocurrents exhibit obvious polarization characteristics. This method's versatility is demonstrated by creating three additional quasi‐2D MHP ferroelectric‐based polarized‐sensitive PDs. A proof‐of‐concept for encrypted optical communication is achieved using the UV‐sensitive PDs as light‐sensing units. These findings highlight FPPE's potential to enhance ferroelectric device polarization control, enabling high‐performance and self‐powered polarization photodetection.